Changing the landscape in solvent extraction - Moyer, Bruce A. (Boca Raton, FL : CRC Press, 2020)
This volume will capture transformational changes in both the chemistry and engineering side of solvent extraction, creating new directions and deepening our understanding of the structure and dynamics of liquid-liquid systems from the molecular- to nano- to meso- to bulk-scale. Reviews will cover advances in microfluidics, new tools for understanding the structure and dynamics of the liquid-liquid interface, ionic liquids in liquid-liquid extraction, molecular dynamics to visualize interactions in the solvent phase, liquid-liquid electrochemistry to interrogate the energetics of interfacial transport and complexation, design of new extractants, and the streamlining of process applications.
X-ray studies of liquid interfaces for solvent extraction.Microfluidics.Task-specific ionic liquids for liquid-liquid extraction.Aqueous complexants.Drop-based modelling of extraction equipment.Recent advances in solvent extraction: from the molecule to the process. What can we learn from the studies of electrochemical processes at the interface between immiscible liquids?
Includes index.
OCLC-licensed vendor bibliographic record.
Keywords: SCIENCE / Chemistry / General; SCIENCE / Chemistry / Analytic; SCIENCE / Chemistry / Physical & Theoretical; Solvent extraction